Odpowiedzi

  • Użytkownik Zadane
2010-04-14T16:07:38+02:00
A) (-15):3-5*(-1)
-3+5=2
b) 3*(-7)-7*(-2)
-21+14=-7
c) 6*(-4)+5*(-9)
-24-45=-69
d) (-18):9-(-27):(-1)
-2-27=-29
Najlepsza Odpowiedź!
2010-04-14T16:07:45+02:00
A) (-15):3-5*(-1)= -5+5= 0
b) 3*(-7)-7*(-2)= -21+14= -7
c) 6*(-4)+5*(-9)= -24-45= -69
d) (-18):9-(-27):(-1)= -2-27= -29
2010-04-14T16:09:31+02:00
A) (-15):3-5*(-1)=-5-(-5)= -5+5=0
b)3*(-7)-7*(-2)=-21-(-14)=-21+14=-7
c)6*(-4)+5*(-9)=-24+(-45)=-24-45=-69
d)(-18):9-(-27):(-1)=-2-27=-29